The science of vaccine adjuvants - O'Hagan, Derek (Henry Stewart Talks, 2023)
Best approaches for adjuvant discovery, Optimal ways to develop vaccine adjuvants, Aluminium adjuvant, Oil/water (o/w) emulsions, Alpha-tocopherol, TLR7 agonists, Small molecule immune potentiators, Liposomes